CORRESPONDENCE OF VENETIAN EMISSARIES IN CONSTANTINOPLE: TURKISMS IN THEIR EPISTLES AND THEIR LINGUISTIC FORMS IN THE BALKANS - KSENIJA AYKUT; MARIJA MITIĆ (Истраживања)
The political and trade ties between the Ottoman Empire and the Venetian Republic from the sixteenth to the eighteenth century significantly impacted cultural history and linguistic development. Skilled in the Ottoman language and the art of drafting official epistles, Venetian dragomans facilitated the incorporation of many Ottoman words into Italian, where they persist today. This linguistic exchange is documented in the reports of Venetian envoys in Constantinople, who recorded numerous Turkisms, including, political and economic terminology in particular and terms denoting occupations in the Ottoman Empire. Many of these Turkisms have remained in use in the Balkans. These reports are therefore vital cultural artifacts and valuable sources for researching culture, literature, and linguistics in Turkey, Italy, and the Balkans.